Learning How to Learn Languages : A Transformative Learning Approach to Empower Effective Language Learners. - Eisenchlas, Susana A.; Shoecraft, Kelly (Student Success v.15 n.1 p.105-113 https://doi.org/10.5204/ssj.3034, 2024)
This practice report describes a 12-week stand-alone course designed to address the challenges university students face in foreign language classes. Adopting principles of transformative language learning, course content, activities and resources were designed and implemented to dispel myths and preconceptions regarding language instruction, promote self-directed, independent learning, and raise awareness of the cognitive and socio-emotional processes involved in language learning. Students' feedback indicate that the course had a significant impact on their perceptions of adult language learning, their capacity to reflect on their use of strategies, and the importance of developing a plan to continue applying these new understandings in their academic pursuits. The course fostered a shift in students' perspective, from viewing themselves as passive recipients of 'language injections', to becoming self-directed, motivated, and independent learners. [Author abstract]